An Interactive Geriatric Denture Case Study Approach Engaging Dental Students Designed to Link Oral Health, Nutrition and Patient Counseling in an Interprofessional Setting - Moshtagh Farokhi (Association of American Medical Colleges, 2015)
Abstract Introduction This comprehensive case-based study simulates a typical dental school edentulous patient, Rosa. Rosa's case is a road map to accessing resources and embedded course materials regarding denture patients while answering test questions. For educators, the case demonstrates how to create a unique delivery method of distributing course information in an alternative teaching modality. The case also shows how student engagement with virtual case-based learning is achievable as a supplement to conventional classroom lectures. It also serves as a prelude to critical thinking instructional strategy for courses with clinical implications. Methods The case was initially piloted with a group of 10 sophomore dental students as a preclinical teaching exposure at the University of Texas Health Science Center at San Antonio Dental School. It took 1 full hour for five groups of student teams to explore the case and ask any questions. Upon completion of the case, an open-ended evaluation was administered to the students. Results The students managed to maneuver the case with ease, and their queries were related to quiz questions embedded in the case. Student responses to the evaluation indicate that the central objectives of this case-based tool have been met. Discussion The Rosa instructional module provides an interprofessional approach aiming to help dental students identify oral health risk factors associated with their edentulous patients. Upon completion of the case, students are able to review medical, social, and dental histories and recognize systemic disease interventions related to oral health, in particular, that of geriatric patients. They can then determine patients' adequate nutritional needs, locate appropriate educational materials and handouts, and develop a tobacco-cessation strategy. Rosa's case enables dental students to familiarize themselves with patient-management skills prior to the actual clinical experience. With modification to its methodology, it can also benefit medical, nursing, dental hygiene, and other allied health students.